Business strategy and firm performance: a multi-industry analysis. Issue 3 (15th August 2016) - Anwar, Jamil; Hasnu, SAF
Abstract : Purpose: The purpose of this paper is to investigate the strategy-performance relationship in a multi-industry setting for joint stock firms operating in Pakistan using Miles and Snow typology. The impact of firm size and industry on performance along with strategy is also investigated. The empirical research evidence on strategy-performance relationship for Miles and Snow typology is updated as well. Design/methodology/approach: Scoring methodology is applied for identification of strategic types, including the reactor strategy. The consistency of the firms over time is also checked. Seven year archived financial data of 320 Pakistani joint stock firms from 12 industries are used for analysis. Descriptive statistics and ANOVA is used for analysis. Findings: Hybrid strategies are practiced by firms rather than pure strategies. The distribution of strategic types is uneven. There are mixed results for performance difference among strategic types for different industries and firm size. Defending and analyzing strategies are better than the prospecting strategies. Reactors performed better in some industries as well. Originality/value: Proposed scoring methodology can be applied to identify all strategic types including reactors in the longitudinal studies. This can be replicated for other typologies or strategic group classifications. The process for identification of reactor strategy through a consistency check is a unique contribution to the literature, especially when archived financial data is used.